Preparation process of halogen-free flame-retardant high-strength polycarbonate composite material

By modifying polycarbonate with cationic DOPO carbonate-based polymer flame retardants and sodium triazine benzene sulfonate-modified carbon nanotubes, the problems of poor compatibility and mechanical properties were solved, and high strength was achieved. and highly flame-retardant polycarbonate composites.

CN118834513BActive Publication Date: 2025-01-24DONGGUAN GANGHUA POLYMER TECH CO LTD

Patent Information

Application Number
CN202411143305.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-01-24
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The poor compatibility of carbon nanotubes with polycarbonate leads to poor flame retardant and mechanical properties of polycarbonate.

Method used

By preparing cedic DOPO carbonate polymer polymer flame retardant and sodium triazine phenylsulfonate, it is used as a filler to fill the polycarbonate to improve the compatibility and mechanical properties.

Benefits of technology

It significantly improves the stretching performance and impact strength of polycarbonate, while improving its flame retardant performance, so that it can show good fire resistance at high temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118834513B_ABST
    Figure CN118834513B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polycarbonate, and discloses a preparation process of a halogen-free flame-retardant high-strength polycarbonate composite material, wherein a DOPO dicarbonate ethyl chloride intermediate and N,N,N',N'-tetramethylethylenediamine are reacted to obtain a cationic DOPO carbonate-based polymer flame retardant. Then, the carbon nanotubes are modified with sodium triazine benzenesulfonate to blend and modify the polycarbonate. The polymer flame retardant contains the same carbonate structural unit as the polycarbonate, and the two have good structural similarity and compatibility, and will not affect the mechanical properties of the polycarbonate. At the same time, the interface interaction and compatibility between the carbon nanotubes and the polycarbonate are improved, and the tensile properties and impact strength of the polycarbonate are improved. The polymer flame retardant contains a DOPO flame retardant group, and the surface of the carbon nanotube contains a triazine functional group and a sulfonate group, which significantly improves the flame retardant properties of the polycarbonate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polycarbonate, in particular to a preparation process of a halogen-free flame-retardant high-strength polycarbonate composite material. Background Art

[0002] Polycarbonate is a thermoplastic engineering material with excellent comprehensive performance. It has the advantages of strong heat resistance, good weather resistance, high chemical stability, and easy processing. It is widely used in electronic appliances, automobile manufacturing, medical equipment, packaging materials and other fields. Although polycarbonate has a certain self-extinguishing property, it is difficult to meet the practical application in high flame retardant and fireproof materials. Therefore, it is necessary to add flame retardants to improve its flame retardant properties. Common flame retardants for polycarbonate include sulfonate flame retardants, nitrogen and phosphorus flame retardants, halogen-containing flame retardants, etc. Such as 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and its derivatives, 1-butyl-3-methylimidazole methanesulfonate ionic liquids, etc., which have the advantages of good flame retardant effect and green environmental protection. However, halogen-containing flame retardants are more polluting. Therefore, it is necessary to develop new environmentally friendly halogen-free flame retardants for polycarbonate.

[0003] As a nanomaterial with excellent performance, carbon nanotubes are widely used in polymer materials such as polycarbonate, polyethylene, polypropylene, and rubber. The research focus is to modify the surface of carbon nanotubes organically, improve their dispersibility, and improve their compatibility with polymer material matrices. Chinese patent CN117285809B discloses that polycarbonate, acrylonitrile-butadiene-styrene copolymer, polyphenylene sulfide, modified multi-walled carbon nanotubes, fluorine-containing anti-drip agents, modified phosphorus-containing flame retardants, etc. are used as raw materials to obtain a new polycarbonate composite material with good mechanical properties, high flame retardancy and weather resistance; however, the patent uses halogen-containing anti-drip agents such as polytetrafluoroethylene, polyfluoroether, and polyvinyl fluoride, which cause greater pollution when burned. Summary of the invention

[0004] The invention solves the problem of poor compatibility between carbon nanotubes and polycarbonate, and the problem of poor flame retardancy and mechanical properties of polycarbonate.

[0005] The technical solution of the present invention is: a preparation process of a halogen-free flame-retardant high-strength polycarbonate composite material:

[0006] Step A, add ethanol, DOPO dicarbonate ethyl chloride intermediate, N,N,N',N'-tetramethylethylenediamine into a flask, heat to 75-80°C, stir and react for 18-24h, condense during the reaction and reflux, rotary evaporate, wash with water, and dry to obtain a cationic DOPO carbonate-based polymer flame retardant.

[0007] The DOPO dicarbonate ethyl chloride intermediate has the following structural formula (I):

[0008]

[0009] Step B: Add solvent, cyanuric chloride modified carbon nanotubes, sodium p-aminobenzenesulfonate, and N,N-diisopropylethylamine into a flask, heat to 60-90° C., react for 20-30 hours, rotary evaporate, wash with tetrahydrofuran and water in sequence, and dry to obtain sodium triazine benzenesulfonate modified carbon nanotubes.

[0010] Step C, adding polycarbonate, cationic DOPO carbonate-based polymer flame retardant, and sodium triazine benzene sulfonate modified carbon nanotubes in a ratio of 100g:(0.2-1.5)g:(0.5-3)g into a twin-screw extruder, melt blending, the melt temperature is 250°C, the screw speed is 50r / min, and extrusion is performed to obtain a halogen-free flame retardant high-strength polycarbonate composite material.

[0011] Furthermore, in step A, the ratio of DOPO dicarbonate ethyl chloride intermediate and N,N,N',N'-tetramethylethylenediamine is (1-1.1) mol:1 mol.

[0012] Furthermore, the preparation process of the DOPO dicarbonate ethyl chloride intermediate is as follows: add dichloromethane, 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, chloroethyl chloroformate, and triethylamine in a ratio of 1 mol:(2-2.5) mol:(2-2.5) mol to a flask under an ice bath, stir the reaction at 15-25° C. for 10-18 hours, distill under reduced pressure, wash with n-hexane, and recrystallize the product with ethyl acetate to obtain the DOPO dicarbonate ethyl chloride intermediate.

[0013] Furthermore, in step B, the solvent is tetrahydrofuran, 1,4-dioxane or toluene.

[0014] Furthermore, in step B, the ratio of cyanuric chloride modified carbon nanotubes, sodium p-aminobenzenesulfonate, and N,N-diisopropylethylamine is 1 g:(13-18) g:(15-21) g.

[0015] Furthermore, the preparation process of cyanuric chloride modified carbon nanotubes is as follows: add water, hydroxylated carbon nanotubes, and sodium hydroxide into a flask, disperse by ultrasound, add an aqueous solution of cyanuric chloride under an ice bath, stir for reaction, filter, wash, and dry to obtain cyanuric chloride modified carbon nanotubes.

[0016] The technical effect of the present invention is as follows: the present invention utilizes 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide and chloroethyl chloroformate to react to obtain a DOPO dicarbonate chloroethyl ester intermediate, which contains two chloroethyl groups, and undergoes a quaternization reaction with N,N,N',N'-tetramethylethylenediamine to polymerize and obtain a novel cationic DOPO carbonate-based polymer flame retardant.

[0017] The invention oxidizes carbon nanotubes with sulfuric acid and nitric acid to obtain hydroxylated carbon nanotubes, and then reacts with cyanuric chloride and sodium p-aminobenzenesulfonate to obtain sodium triazine benzenesulfonate modified carbon nanotubes, thereby modifying the surface of the carbon nanotubes with triazine groups and sodium sulfonate groups.

[0018] The present invention uses cationic DOPO carbonate-based polymer flame retardant and triazine benzene sulfonate sodium modified carbon nanotubes as fillers to fill and modify polycarbonate. The polymer flame retardant contains the same carbonate structural unit as polycarbonate, so that the two have good structural similarity and compatibility, and the addition of the flame retardant will not affect the mechanical properties of the polycarbonate.

[0019] The sodium triazine benzene sulfonate modified carbon nanotubes of the present invention have better dispersibility after being modified with surface organic functional groups. At the same time, the sodium sulfonate groups contained on the surface can electrostatically interact with the quaternary ammonium salt cations in the polymer flame retardant, so that there is a strong interface force between the carbon nanotubes and the polymer flame retardant, so that the polymer flame retardant can be used as a compatibilizer to improve the interface interaction and compatibility between the carbon nanotubes and the polycarbonate, so that the carbon nanotubes significantly improve the tensile properties and impact strength of the polycarbonate.

[0020] The polymer flame retardant of the present invention contains a large amount of DOPO flame retardant groups, which form nitrogen-phosphorus flame retardants with triazine functional groups on the surface of carbon nanotubes modified by sodium triazine benzene sulfonate. When burning, the polycarbonate matrix is ​​dehydrated to form a foam carbon structure. At the same time, the sulfonate groups on the surface of the carbon nanotubes can also catalyze the cross-linking of polycarbonate into carbon. The carbon layer structure has the function of isolating oxygen from contacting the polycarbonate matrix and preventing heat conduction. It also has the functions of suppressing smoke and preventing molten droplets, thereby improving the flame retardant properties of the polycarbonate. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the reaction formula for preparing DOPO dicarbonate ethyl chloride intermediate.

[0022] Figure 2 It is the reaction formula for preparing cationic DOPO carbonate-based polymer flame retardant.

[0023] Figure 3 It is the reaction formula for preparing carbon nanotubes modified by sodium triazine benzene sulfonate. DETAILED DESCRIPTION

[0024] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The materials, reagents, etc. used in the present invention, unless otherwise specified, are conventional commercial products and can be obtained from commercial channels.

[0025] Add 20 mL of concentrated sulfuric acid and 0.2 g of carbon nanotubes into a flask, add 20 mL of concentrated nitric acid after ultrasonic dispersion, heat to 140° C., react for 1 hour, condense and reflux during the reaction, add water to dilute, filter, wash, and dry to obtain hydroxylated carbon nanotubes.

[0026] Add 120 mL of water, 0.5 g of hydroxylated carbon nanotubes, and 0.7 g of sodium hydroxide into a flask, disperse by ultrasound, add 100 mL of an aqueous solution containing 2.2 g of cyanuric chloride under an ice bath, stir and react for 48 hours, filter, wash with water and 1,4-dioxane in turn, and dry to obtain cyanuric chloride-modified carbon nanotubes.

[0027] Example 1

[0028] (1) In an ice bath, add 20 mL of dichloromethane, 4 mmol of 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, 8 mmol of chloroethyl chloroformate, and 8 mmol of triethylamine to a flask, stir and react at 25° C. for 10 h, evaporate under reduced pressure, wash with n-hexane, and recrystallize the product with ethyl acetate to obtain a DOPO dicarbonate chloroethyl ester intermediate.

[0029] (2) Add 50 mL of ethanol, 6.6 mmol of DOPO dicarbonate ethyl chloride intermediate, and 6 mmol of N,N,N',N'-tetramethylethylenediamine into a flask, heat to 75°C, and stir to react for 18 hours. During the reaction, condense and reflux, rotary evaporate, wash with water, and dry to obtain a cationic DOPO carbonate-based polymer flame retardant.

[0030] (3) Add 400 mL of 1,4-dioxane solvent, 2 g of cyanuric chloride-modified carbon nanotubes, 28 g of sodium p-aminobenzenesulfonate, and 30 g of N,N-diisopropylethylamine to a flask, heat to 70°C, react for 24 h, rotary evaporate, wash with tetrahydrofuran and water in turn, and dry to obtain sodium triazine benzenesulfonate-modified carbon nanotubes.

[0031] (4) Add 1 kg of polycarbonate, 2 g of cationic DOPO carbonate-based polymer flame retardant, and 5 g of sodium triazine benzene sulfonate-modified carbon nanotubes into a twin-screw extruder, melt blend, control the melt temperature to 250° C., and the screw speed to 50 r / min, and extrude to obtain a halogen-free flame-retardant high-strength polycarbonate composite material.

[0032] Example 2

[0033] (1) In an ice bath, add 25 mL of dichloromethane, 4 mmol of 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, 10 mmol of chloroethyl chloroformate, and 10 mmol of triethylamine to a flask, stir and react at 15° C. for 18 h, evaporate under reduced pressure, wash with n-hexane, and recrystallize the product with ethyl acetate to obtain a DOPO dicarbonate chloroethyl ester intermediate.

[0034] (2) Add 40 mL of ethanol, 6 mmol of DOPO dicarbonate ethyl chloride intermediate, and 6 mmol of N,N,N',N'-tetramethylethylenediamine into a flask, heat to 80°C, and stir to react for 18 hours. During the reaction, condense and reflux, rotary evaporate, wash with water, and dry to obtain a cationic DOPO carbonate-based polymer flame retardant.

[0035] (3) Add 600 mL of toluene solvent, 2 g of cyanuric chloride-modified carbon nanotubes, 32 g of sodium p-aminobenzenesulfonate, and 36 g of N,N-diisopropylethylamine to a flask, heat to 60° C., react for 30 h, rotary evaporate, wash with tetrahydrofuran and water in turn, and dry to obtain sodium triazine benzenesulfonate-modified carbon nanotubes.

[0036] (4) Add 1 kg of polycarbonate, 8 g of cationic DOPO carbonate-based polymer flame retardant, and 18 g of sodium triazine benzene sulfonate-modified carbon nanotubes into a twin-screw extruder, melt blend, control the melt temperature to 250° C., and the screw speed to 50 r / min, and extrude to obtain a halogen-free flame-retardant high-strength polycarbonate composite material.

[0037] Example 3

[0038] (1) Prepare a cationic DOPO carbonate-based polymer flame retardant according to the method of Example 1.

[0039] (2) Add 600 mL of tetrahydrofuran, 2 g of cyanuric chloride-modified carbon nanotubes, 36 g of sodium p-aminobenzenesulfonate, and 42 g of N,N-diisopropylethylamine to a flask, heat to 90° C., react for 20 h, rotary evaporate, wash with tetrahydrofuran and water in turn, and dry to obtain sodium triazine benzenesulfonate-modified carbon nanotubes.

[0040] (3) Add 1 kg of polycarbonate, 15 g of cationic DOPO carbonate-based polymer flame retardant, and 30 g of sodium triazine benzene sulfonate-modified carbon nanotubes into a twin-screw extruder, melt blend, control the melt temperature to 250° C., and the screw speed to 50 r / min, and extrude to obtain a halogen-free flame-retardant high-strength polycarbonate composite material.

[0041] Comparative Example 1

[0042] (1) Add 1 kg of polycarbonate into a twin-screw extruder, melt-treat, control the melt temperature to 250° C., and rotate the screw at 50 r / min to extrude to obtain a polycarbonate material.

[0043] Comparative Example 2

[0044] (1) Prepare a cationic DOPO carbonate-based polymer flame retardant according to the method of Example 1.

[0045] (2) Add 1 kg of polycarbonate and 2 g of cationic DOPO carbonate-based polymer flame retardant into a twin-screw extruder, melt blend, control the melt temperature to 250° C., and the screw speed to 50 r / min, and extrude to obtain a halogen-free flame-retardant high-strength polycarbonate composite material.

[0046] Comparative Example 3

[0047] (1) Prepare triazine benzene sulfonate modified carbon nanotubes according to the method of Example 1.

[0048] (2) Add 1 kg of polycarbonate and 5 g of sodium triazine benzene sulfonate-modified carbon nanotubes into a twin-screw extruder, melt blend, control the melt temperature to 250° C., and the screw speed to 50 r / min, and extrude to obtain a halogen-free flame-retardant high-strength polycarbonate composite material.

[0049] Comparative Example 4

[0050] (1) Prepare triazine benzene sulfonate modified carbon nanotubes according to the method of Example 1.

[0051] (2) Add 1 kg of polycarbonate, 2 g of 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, and 5 g of sodium triazine benzenesulfonate modified carbon nanotubes into a twin-screw extruder, melt blend, control the melt temperature to 250° C., and the screw speed to 50 r / min, and extrude to obtain a halogen-free flame retardant high-strength polycarbonate composite material.

[0052] Comparative Example 5

[0053] (1) Prepare a cationic DOPO carbonate-based polymer flame retardant according to the method of Example 1.

[0054] (2) Add 1 kg of polycarbonate, 2 g of cationic DOPO carbonate-based polymer flame retardant, and 5 g of hydroxylated carbon nanotubes into a twin-screw extruder, melt blend, control the melt temperature to 250° C., and the screw speed to 50 r / min, and extrude to obtain a halogen-free flame-retardant high-strength polycarbonate composite material.

[0055] The polycarbonate composite material is placed in a molding machine and molded at 250° C. under a pressure of 15 MPa to form a polycarbonate sheet.

[0056] The impact strength is tested according to GB / T 1843-2008 standard.

[0057] Cut the polycarbonate sheet into dumbbell-shaped specimens and test the tensile properties according to GB / T 1040.1-2018. The tensile rate is 20 mm / min.

[0058] The flame retardant properties are tested according to GB / T 2406.1-2008 and UL94 for limiting oxygen index and vertical burning grade.

[0059] Table 1 Mechanical properties test of polycarbonate

[0060]

[0061] As shown in Table 1, compared with Comparative Example 1, Examples 1, 2, and 3 added cationic DOPO carbonate-based polymer flame retardant and triazine benzene sulfonate-modified carbon nanotubes. The polymer flame retardant contains the same carbonate structural unit as polycarbonate, so that the two have good structural similarity and compatibility, and the addition of the flame retardant will not affect the mechanical properties of polycarbonate. And after the surface organic functional groups of the triazine benzene sulfonate-modified carbon nanotubes are modified, the dispersibility is better, and the sodium sulfonate groups contained on the surface can electrostatically interact with the quaternary ammonium salt cations in the polymer flame retardant, so that there is a strong interfacial force between the carbon nanotubes and the polymer flame retardant, so that the polymer flame retardant can be used as a compatibilizer to improve the interfacial interaction and compatibility between the carbon nanotubes and the polycarbonate, so that the carbon nanotubes significantly improve the tensile properties and impact strength of the polycarbonate.

[0062] In Comparative Example 2, only cationic DOPO carbonate-based polymer flame retardant was added. The polymer flame retardant and polycarbonate have good structural compatibility. The addition of flame retardant will not affect the mechanical properties of polycarbonate. Compared with Comparative Example 1, the difference in tensile properties and impact strength between the two is very small. However, no sodium triazine benzene sulfonate modified carbon nanotubes were added, and the tensile properties and impact strength were significantly lower than those in Example 1.

[0063] In Comparative Example 3, no cationic DOPO carbonate-based polymer flame retardant was added, and only sodium triazine benzene sulfonate-modified carbon nanotubes were added. After the carbon nanotubes were modified with organic functional groups, the dispersion was good, and the polycarbonate had a good reinforcement effect. The tensile properties and impact strength were significantly higher than those in Comparative Example 1. However, no cationic DOPO carbonate-based polymer flame retardant was added as a compatibilizer, and the interface interaction and compatibility between the carbon nanotubes and the polycarbonate were not further improved, resulting in the reinforcement effect of the carbon nanotubes being lower than that in Example 1, and the tensile properties and impact strength being lower than those in Example 1.

[0064] Compared with Comparative Example 3, Comparative Example 4 adds 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide as a flame retardant. Due to the poor compatibility of the flame retardant with polycarbonate, the addition has a greater impact on the mechanical properties of the polycarbonate, and the tensile properties and impact strength are lower than those of Comparative Example 3, and are also lower than those of Example 1.

[0065] In Comparative Example 5, ordinary hydroxylated carbon nanotubes are added, which have poor compatibility with polycarbonate and do not contain sodium sulfonate groups. They cannot electrostatically interact with the cationic DOPO carbonate-based polymer flame retardant, so that the flame retardant has no volume expansion effect and does not improve the interfacial interaction and compatibility between the carbon nanotubes and the polycarbonate, resulting in the reinforcement effect of the carbon nanotubes being lower than that of Example 1, and the tensile properties and impact strength being lower than those of Example 1.

[0066] Table 2 Table 1 Polycarbonate flame retardant performance test

[0067] Limiting oxygen index (%) UL-94 Rating Example 1 28.5 V-0 Example 2 31.7 V-0 Example 3 33.4 V-0 Comparative Example 1 25.7 V-2 Comparative Example 2 27.5 V-1 Comparative Example 3 26.8 V-1 Comparative Example 4 28.7 V-0 Comparative Example 5 27.9 V-1

[0068] As shown in Table 2, the limiting oxygen index of the polycarbonate of Examples 1-3 reaches 28.5-33.4%; the vertical combustion grade of UL-94 reaches V-0, showing good flame retardant performance. This is because the polymer flame retardant contains a large amount of DOPO flame retardant groups, which form nitrogen-phosphorus flame retardants with the triazine functional groups on the surface of the carbon nanotubes modified by sodium triazine benzene sulfonate, and dehydrate the polycarbonate matrix to form a foam carbon structure during combustion. At the same time, the sulfonate groups on the surface of the carbon nanotubes can also catalyze the cross-linking of polycarbonate into carbon. The carbon layer structure has the function of isolating oxygen from contacting the polycarbonate matrix, preventing heat conduction, and has the function of suppressing smoke and preventing melting drops, thereby improving the flame retardant performance of polycarbonate.

[0069] Comparative Example 2 did not add sodium triazine benzene sulfonate modified carbon nanotubes, and Comparative Example 3 did not add cationic DOPO carbonate-based polymer flame retardant, resulting in the limiting oxygen index of the polycarbonate being lower than that of Example 1, and the vertical burning rating of UL-94 being V-1.

[0070] The hydroxylated carbon nanotubes added in Comparative Example 5 do not contain triazine functional groups and sulfonate flame retardant groups, resulting in the limiting oxygen index of the polycarbonate being lower than that of Example 1, and the vertical burning rating of UL-94 being V-1.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A process for preparing a halogen-free flame-retardant high-strength polycarbonate composite material, characterized in that: The preparation process comprises the following steps: step A, adding ethanol, DOPO dicarbonate ethyl chloride intermediate, and N,N,N',N'-tetramethylethylenediamine into a flask, stirring for reaction, rotary evaporation, water washing, and drying to obtain a cationic DOPO carbonate-based polymer flame retardant; The DOPO dicarbonate ethyl chloride intermediate has the following structural formula (I): Formula (I); Step B, adding a solvent, cyanuric chloride modified carbon nanotubes, sodium p-aminobenzenesulfonate, and N,N-diisopropylethylamine into a flask, performing rotary evaporation after the reaction, washing with tetrahydrofuran and water in sequence, and drying to obtain sodium triazine benzenesulfonate modified carbon nanotubes; Step C, adding polycarbonate, cationic DOPO carbonate-based polymer flame retardant, and sodium triazine benzene sulfonate-modified carbon nanotubes into a twin-screw extruder, melt blending, and extruding to obtain a halogen-free flame-retardant high-strength polycarbonate composite material; In the step A, the ratio of DOPO dicarbonate ethyl chloride intermediate and N,N,N',N'-tetramethylethylenediamine is (1-1.1) mol:1 mol; In the step B, the ratio of cyanuric chloride modified carbon nanotubes, sodium p-aminobenzenesulfonate, and N,N-diisopropylethylamine is 1 g: (13-18) g: (15-21) g; In the step C, the ratio of polycarbonate, cationic DOPO carbonate-based polymer flame retardant, and sodium triazine benzene sulfonate modified carbon nanotubes is 100 g: (0.2-1.5) g: (0.5-3) g.

2. The process for preparing the halogen-free flame-retardant high-strength polycarbonate composite material according to claim 1, characterized in that: In the step A, the reaction temperature is 75-80°C and the reaction time is 18-24h.

3. The preparation process of the halogen-free flame-retardant high-strength polycarbonate composite material according to claim 1, characterized in that: The preparation process of the DOPO dicarbonate ethyl chloroester intermediate is as follows: dichloromethane, 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, chloroethyl chloroformate and triethylamine are added to a flask under an ice bath, the mixture is stirred at 15-25° C. for 10-18 hours, the mixture is distilled under reduced pressure, washed with n-hexane, and the product is recrystallized with ethyl acetate to obtain the DOPO dicarbonate ethyl chloroester intermediate.

4. The process for preparing the halogen-free flame-retardant high-strength polycarbonate composite material according to claim 3, characterized in that: The ratio of the 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, chloroethyl chloroformate and triethylamine is 1 mol:(2-2.5) mol:(2-2.5) mol.

5. The process for preparing the halogen-free flame-retardant high-strength polycarbonate composite material according to claim 1, characterized in that: In the step B, the solvent is tetrahydrofuran, 1,4-dioxane or toluene.

6. The process for preparing the halogen-free flame-retardant high-strength polycarbonate composite material according to claim 1, characterized in that: In the step B, the reaction temperature is 60-90° C. and the reaction time is 20-30 hours.

7. The process for preparing the halogen-free flame-retardant high-strength polycarbonate composite material according to claim 1, characterized in that: The preparation process of the cyanuric chloride modified carbon nanotubes is as follows: water, hydroxylated carbon nanotubes and sodium hydroxide are added into a flask, ultrasonic dispersion is performed, an aqueous solution of cyanuric chloride is added under an ice bath, stirring for reaction, filtering, washing and drying are performed to obtain the cyanuric chloride modified carbon nanotubes.

Citation Information

Patent Citations

  • A new flame-retardant and weather-resistant polycarbonate composite material and its preparation process

    CN117285809B

  • Preparation method of flame-retardant high-hardness epoxy resin floor paint

    CN114350230A

  • Preparation method of halogen-free flame-retardant polycarbonate plastic

    CN115746536A

Cited By

  • Fluoride-free halogen-free flame-retardant polycarbonate material as well as preparation method and application thereof

    CN120842823A